ANALYSIS OF IMPLEMENTATION OF PSAK 45 CONSERNING THE PREPARATION AND PRESENTATION OF FINANCIAL STATEMENT OF NON PROFIT ORGANIZATIONS AT STATE SMA 17 BATAM - FITRI MISWATI; Kardi; Muhammad Rinjani (LP2M-Institut Agama Islam Abdullah Said Batam, 2022)
The purpose of this study is to complie and present the financial statement of non-profit orgizations at SMA N 17 Batam in accordance with PSAK No. 45. The type of research used is description research with the data needed is primary data in the form of Communittee Donation Acceptance data, RAPBS, asset list, and realization of RAPBS obtained from SMA N 17 Batam . Data collection methods used in this study interviews and documentation with qualitative description data analysis. The results of this study indicate that the financial statement at SMA N 17 Batam is not in accordance with the preparation of financial statements vased on the format of financial statement of non-profit organization that exist in PSAK No. 45 SMA N 17 Batam does not present a statement of financial position, activity report, cash flow statement, and notes to financial statements. The preparation of the financial statement of SMA 17 Batam should be guided. Existing financial reports are in the form expenses report are in the form of expenses reports, RAPBS reports and RAPBS realization reports. SMA N 17 Batam also does not evaluate fixed assets and calculate despreciation on fixed assets, so the value of fixed assetes does not show the actual value.